Neuromuscular, biochemical, performance and perceptual responses following a self-paced soccer match simulation - Tofari, P.; Kemp, J.; Cormack, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Aim: A soccer match is characterised by high-intensity, intermittent running, including directional changes, rapid accelerations and decelerations, resulting in both biological and psychological disturbance. Match simulations used to assess responses in a controlled environment lack ecologically validity due to external pacing. Recently, an ecologically valid and reliable self-paced protocol has been developed using a non-motorised treadmill (NMT). The aim was to assess the neuromuscular, biochemical, performance and perceptual responses to that protocol. Method: Twelve male team-sport athletes (24.5±3.9 y, 76.8±5.1 kg, VO2peak 52.3±4.0 ml/kg/min) performed a self- paced 90-min match simulation on a NMT. Match running performance and the following variables were collected Pre-, Half-time (except blood), Post-, 2-h post-, and 1-4 days post-match: - Quadriceps function via a maximal voluntary contraction and magnetic stimulation assessing central (voluntary activation) and peripheral (potentiated twitch torque) fatigue - Endocrine response (testosterone and cortisol), oxidative stress (uric acid) and muscle damage [creatine kinase (CK)] - Countermovement jump, squat jump (SJ) and isometric mid-thigh pull (IMTP) performance - Rating of perceived exertion and self-report wellness questionnaire Statistical analysis included magnitude of change calculations between time points compared to pre-match using effect size statistics (±90% CL) and regression analysis. Results: Participants covered 12445.8±768.7m at 87.1±3.2% maximal HR, similar to actual match observations. Central and peripheral fatigue was evident at Half-time (-0.38±0.46 and -0.79±0.30, respectively) and persisted post-match. SJ height was reduced at Half-time (-0.42±0.31) and persisted until Day 4. Perceptual fatigue and soreness peaked at Day 1 (-0.92±0.88 and - 1.49±0.76, respectively), as did CK (123.4±70.8%). Significant relationships arose between numerous variables, including high speed running and soreness (r=0.65), very high speed running and potentiated twitch torque (r=-0.78) and IMTP F.kg-1 Pre with change in CK (r=-0.58 to -0.81). Discussion: The current protocol allowed detection of central and peripheral fatigue at half time, which has not been previously reported, and this magnitude of change was not increased post-match. Similar to previous work, there was disturbance to numerous systems, generally returning to baseline in 3 days. Relationships exist between activity profile and perceptual and neuromuscular variables, and higher maximal lower-body strength resulted in less muscle damage post-match. The findings warrant further investigation into the role of central and peripheral fatigue in regulating second half performance and potential interventions to minimise any negative impacts.